EFEKTIFITAS UJIAN MADRASAH BERBASIS COMPUTER BASED TEST DI MADRASAH IBTIDAIYAH SWASTA PILADANG - Marlina, Silvia; Supratman (Cerdas Proklamator, 2023)
This study aims to describe the effectiveness of the madrasah exam with a computer-based test (CBT) system and prepare students to take the CBT madrasa exam, the effective use of CBT in the implementation of the Madrasah Exam at MIS Piladang, Lima Puluh Kota Regency.. The subjects of this study were the Madrasah Examination Implementation Committee, teachers and students. The object of this research is the use of CBT in the implementation of Madrasah Exams. This research is descriptive using a qualitative approach. Data was collected by means of observation, interviews, questionnaires and documents. The data analysis phase includes data reduction, data presentation, and drawing conclusions. The results of this study indicate that the process of using computers and paper-based systems in the implementation of the Madrasah Examination at MIS Piladang has been going well through the planning and implementation stages. Preparation of students according to the Madrasah Exam is good 90%. Student responses have been positive, students are ready to take the CBT Madrasah Exam at MIS Piladang. Preparation of students can be seen from many aspects, namely physical, mental, emotional and knowledge conditions. The use of CBT is considered effective because it has fulfilled several aspects, namely validity, reliability, purpose, practicality and economy. Keywords: Effectiveness, Madrasah Exams, Computer Based Tests, Private Islamic Schools